Making a little affinity go a long way: a topological view of LFA-1 regulation. - Dustin, M (1998)
Lymphocytes utilize adhesion to navigate in the body and to transiently interact with a variety of potential antigen presenting cells. Interactions of adhesion molecules are governed by the law of mass action and the less understood rules of apposed biological membranes. Biochemical parameters such as adhesion molecule affinity only tell part of the story. Factors such as lateral mobility, membrane alignment and cytoskeletal interactions are equally important in determining the final outcome. Therefore it is important to determine mechanisms by which the properties of cell membranes and the cytoskeleton reinforce or hinder adhesion molecule interactions. Work from my lab has shown that one mechanism by which lymphocyte adhesion molecules cooperate is to align adhering membranes with nanometer precision. Here, I discuss a model for LFA-1 regulation that is dependent on three independent processes: LFA-1 lateral mobility, ligand induced generation of a small amount of high affinity LFA-1 and local membrane alignment. I propose that coordination of these processes allows rapid interconversion between stable adhesion and detachment.